Microstructural evolution, mechanical and wear properties, and corrosion resistance of as-cast CrFeNbTiMox Refractory high entropy alloys. (April 2023) - Chen, Ba; Li, Xinmei; Chen, Wenjie; Shang, Li; Jia, Liming
Abstract: In this paper, a series of novel CrFeNbTiMox (x=0.2, 0.4, 0.6, 0.8, 1) refractory high entropy alloys (RHEAs) were fabricated. The effects of different Mo content on the microstructure evolution, mechanical properties, wear and corrosion resistance were investigated. As the increasing of Mo content, the microstructure of the alloy was BCC phase (body-centered cubic Im3m), C14-Laves (P63/MMC) and C15-Laves (Fd3m) as revealed by XRD and electron back-scattered diffraction (EBSD). Apart from the disordered BCC phase, another ordered B2 phase (Pm3m) also appeared in RHEAs. The final experiment showed: Uniaxial compression and microhardness tests revealed that the compressive strength and Vickers microhardness of the RHEAs were in the range 350–800 MPa and 800–931 HV, respectively, and increased with increasing Mo content. Electrochemical tests in a 3.5 wt.% NaCl solution showed that the RHEAs exhibited a significantly corrosion resistance. The sample Mo1 exhibited the highest Ecorr and smallest icorr and therefore the best corrosion resistance. The wear rate and coefficient of friction of the RHEAs increased with increasing Mo content. The sample Mo1 exhibited the lowest wear rate and coefficient of friction of 0.6 mg and 0.6255, respectively. The RHEAs synthesized in this work, especially Mo1, exhibited a high strength and excellent corrosion and wear resistance. Therefore, they have immense potential for various engineering applications. Graphical abstract: First of all, a series of CrFeNbTiMox refractory high entropy alloys (RHEAs) were prepared. The different crystal structures of each constituent, the RHEAs exhibited body centered cubic (BCC) phase and Laves phase structures as revealed by X-ray diffraction and electron back-scattered diffraction.Besides, at room temperature with the increase of Mo content, the mechanical properties of the CrFeNbTiMox alloy are significantly improved. When x = 1, the yield strength of CrFeNbTiMo is the highest, which is 785 MPa. Under the dynamic compression load, the strength of the CrFeNbTiMox alloy reaches 1035 Mpa when x = 1.Finally, the average friction coefficients of the five RHEAs gradually decreased with increasing Mo content. With the results of dynamic polarization curve analysis, the five RHEAs show excellent corrosion resistance. Image 1 Highlights: CrFeNbTiMox RHEAs consist of BCC and Laves phases. The addition of Mo inhibited the formation of Laves phase of the CrFeNbTiMox RHEAs. The addition of Mo can improve the mechanical properties of the CrFeNbTiMox RHEAs. The addition of Mo can improve the corrosion and wear properties of the CrFeNbTiMox RHEAs.